Effect of chronic training on heart rate variability, salivary IgA and salivary alpha-amylase in elite swimmers with a disability - Edmonds, R.; Burkett, B.; Leicht, A.; McKean, M. (PLOS ONE, 2015)
The purpose of this study was to a) determine the heart rate variability (HRV) and saliva markers of immunity (salivary immunoglobulin A; sIgA) and stress (salivary alpha-amylase; sAA) responses to chronic training in elite swimmers with a disability; and b) identify the relationships between HRV, sIgA, sAA and training volume. Eight members of a high performance Paralympic swimming program were monitored for their weekly resting HRV, sIgA and sAA levels in the 14 weeks leading up to a major international competition. The 14 week training program included aerobic, anaerobic, power and speed, and taper training phases, while also incorporating two swimming step tests and two swimming competitions. Specific time (root mean square of the successive differences; RMSSD) and frequency (high frequency normalized units [HFnu]) domain measures, along with non-linear indices (standard deviation of instantaneous RR variability; SD1 and short term fractal scaling exponent; a1) of HRV were used for all analyses with effects examined using magnitude-based inferences. Relationships between HRV and saliva markers were identified by Spearman rank rho correlation coefficients. Compared with week 1, SD1 was very likely lower (96/4/0, ES = -2.21), while sAA was very likely elevated (100/0/0, ES = 2.32) at the beginning of week 7 for all athletes. The training program did not alter HRV or saliva whereas competition did. There were also no apparent differences observed for HRV, sIgA and sAA between each of the training phases during the 14 week swimming program. Correlations were observed between sAA and SD1 (rho = -0.212, p<0.05), along with sAA and mean HR (rho = 0.309, p<0.05). These results show that high level national competition influences depresses HRV (SD1) and increases saliva biomarkers of stress (sAA). It appears that a well-managed and periodised swimming program can maintain these indices within normal baseline levels. The study also highlighted the parasympathetic nervous system influence on sAA.